Design, synthesis, and properties of nonlinear optical chromophores based on a verbenone bridge with a novel dendritic acceptor. Issue 11 (6th March 2018) - Sun, Hejing; Li, Zhong'an; Wu, Jieyun; Jiang, Zhenhua; Luo, Jingdong; Jen, Alex K.-Y.
Abstract : A polyenic chromophore containing a new dendritic tricyanofuran acceptor has been synthesized for achieving improved polar order in poled polymers. Abstract : Two novel second order nonlinear optical (NLO) chromophores based on N, N -diethylaniline as a donor, verbenone based tetraene as a bridge, and tricyanofuran (TCF) or tricyanofuran derivatives with a dendritic moiety as an acceptor have been synthesized in good overall yields and systematically characterized. Besides, a facile applicable synthetic approach for a NLO dendritic acceptor was developed. Compared withC7, after introducing dendritic derivative steric hindrance groups into the acceptor, chromophoreC8 had good thermal stabilities with high thermal decomposition temperatures which were 33 °C higher than that of chromophoreC7 . At the same time, cyclic voltammetry (CV) experiments were performed to determine the different redox properties. The conjugated verbenone tetraene segments in two chromophores could significantly improve the glass-forming ability and molecular polarization of chromophores as revealed by UV-vis-NIR absorption measurements. The bulky dendritic moiety linked by a short C–C bond is closer to the TCF acceptor, which is the most polar part in the chromophore, compared to conventional isolation groups. The results obtained from electro-optic (EO) coefficients indicate that this TCF acceptor with a unique dendritic structure can prevent antiparallel packing between chromophores, improving the poling efficiency and enhancing the EO performance. These properties, together with the good solubility, suggest the potential use of these new chromophores as materials for advanced photonic devices.